Determinants of Financial Well-Being Among Young Workers in Jakarta During the Covid-19 Pandemic - Margarita Ekadjadja, Pamela Lavonda, Ignatius Roni Setyawan, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to analyze the effect of financial attitudes, financial behavior, and financial literacy on financial welfare. This research model uses convenience sampling technique through distributing questionnaires and collected as many as 163 respondents. The data was processed using the Structural Equation Modeling (SEM) method with smartPLS 3 software. The results indicate that financial attitudes have a positive influence on financial welfare. A good financial attitude can increase awareness to manage finances so as to improve financial well-being. Financial behavior has a positive influence on financial well-being. Good financial behavior encourages people to make long-term plans to cover unforeseen costs which can ultimately improve financial well-being. Financial literacy has a positive influence on financial well-being. Financial literacy not only affects the way individuals manage finances and solve financial problems, but also has implications for the individual's ability to make financial decisions related to investments, savings, and other financial risks. Thus financial prosperity can be achieved.